(untitled) (Konferensiyalar | Conferences, 2024)
Teaching a foreign language is considered one of the most challenging processes, and both teachers and language learners may face various difficulties, especially in speaking skills. The research will discuss the most crucial challenges of teaching speaking skills in English classrooms and how to overcome them in substantial and effective ways.